Terapi Seni Melalui Melukis pada Pasien Skizofrenia dan Ketergantungan Narkoba - Sarie Rahma Anoviyanti (Journal of Visual Art and Design, 2008)
For centuries, human used various forms and/or elements of art as an effort to 'treat' their body and souls. The ancient Greece used the existence of theatrical art as something that has catharsis effect in "cleansing" and/or "healing" their souls. Through this understanding, the author explores the effect of art activities on the process of mental recovery (art therapy). It is observed that through the process, catharsis effect serves as an important part of art therapy; exploring process and activities that unites disciplines of Art and Psychology as means for treatment.